Determining the mutual Interaction factor for Phonon-Exciton in AgBr crystal doped with copper (Latakia University Journal -Basic Sciences Series, 2021)
The essential absorption edge of AgBr doped with copper is investigated and studied   as a function of  temperature, in the temperature range from 140 K to 490 K , and in the energy range from 2 eV to 3.5 eV. The mutual interaction factor  for phonon-  exciton in the crystal is calculated and compared the same factor of intrinsic AgBr .